PENDAPATAN, EFISIENSI USAHA GULA KELAPA DAN PEMASARANNYA DI DESA PAL 30 KABUPATEN BENGKULU UTARA - Marlina, Lenny; Badruddin, Redy; Utama, Satria Putra (Jurnal AGRISEP, 2004)
Plantation   of coconut   under  farmer  cultivation   have  two processing  status owner and share-fanner  processor. This research  target was to know  the level of eamings  and  business  efficiency  of owner fanner  and processor farmer  and  to describe  marketing  channel  fonn  and marketing  margin.  Method  for calculating the efflciency was RIC  ratio  analysis,   while  to test  the difference   of efficiency  among   actots  W8I9 used statistical test u(Mann  -Whitney  test).  Channel Marketing  by  description   and   marketing   margin  calculated  through     seHlng price  marketing  Institute  minus  buying  of marketing  institute  or  expense  institute  marketing   up by profit institute  marketing.                                                                                    Key words:  Income, efficiency, coconut sugar, and marketing